(untitled) (Research, Society and Development, 2020)
Changes in land use and land cover are thought to cause major environmental degradation as the forest is converted into other uses. In the State of Pará, the main activity responsible for deforestation is livestock, so studies should be carried out to identify changes in land use due to environmental protection. For this reason, the objective of this study was to analyze deforestation in the municipality of São Felix do Xingu / Pará. For the development of the study, data provided by the National Institute for Space Research - INPE, which provides daily, monthly and annual data on deforestation and degradation rates in Brazilian regions and which activities are explored, were used. From this, it was identified that in recent years the rate of deforestation only grows in a variable and rapid manner over time, with 54,167.5 km² of devastated area between the years 2010 to 2019. Only in 2010 did the Xingu territory obtain 20.18% of destruction caused in forest areas. It is noticed that in 2015, the numbers jumped to 21.23% compared to 2010 and, thus, the values continue to maximize in 2019, hovering around 22.88%. With the temporal analysis it was possible to observe new fronts of deforestation that are heading towards Northeast, Northwest (parallel to the Xingu River) and West (entering towards Terra do Meio). Therefore, there must be greater inspection by public bodies in these areas, since illegal exploitation and pressure for natural resources are increasing over the years.